STUDI PERKUATAN GEOTEXTILE PADA LERENG DENGAN VARIASI KEMIRINGAN DAN JARAK PONDASI DANGKAL MELALUI PEMODELAN DI LABORATORIUM - Edo Caraka Yodha; Arief Alihudien; Pujo Priyono (Universitas Muhammadiyah Jember, 2019)
Indonesia is a country in a period of growing development where the infrastructure is built not off of the ground inclined plane or slope, such as housing construction and the manufacture of the Embankment to the road Toll. Responding to the incident the author conducted the analysis of stability of slopes with and without reinforcement through modeling in the laboratory. There are several types of soil reinforcement, use reinforcement Geotextile, the use of a Geotextile can increase the stability of the slope. This study aims to determine the stability of the slopes against the influence of the three variations of the distance of loading a shallow foundation and three variations of the slope. Testing in this study are divided into 2 kinds of models, namely: (1) Testing the Model I is test 2 variations of the distance of loading and 3 variations of the slope of the ground without the use of reinforcement Gotextile Woven (2) Testing the Model II is a test of the 2 variations of the distance of loading and 3 variations of the slope of the land with the use of reinforcement Gotextile Woven. In a review of 3 (three) variations of the slope, namely: 45º, 50º, and 60º, as well as 2 (two) variations of the distance of the load acting on the slope, namely: 4 cm and 7 cm. On the modeling of the soil before repaired using Geotextile can be seen that the smaller the angle kelerengannya, then the power capacity of the soil is correlated with soil stiffness is of great value. While the modeling of soil after repaired using Geotextile the smaller the angle kelerengannya, then the power capacity of the soil is correlated with the stiffness of the soil of little value. On the modeling of the soil before repaired using Geotextile can be seen that the farther the distance of loading from the lips of the slopes, then the power capacity of the soil is correlated with soil stiffness is of great value. While the modeling of soil after repaired using Geotextile the greater the distance of loading from the lips of the slopes, then the power capacity of the soil is correlated with the stiffness of the soil of little value. Can in the analogy that the repair of soil slopes using Geotextile has the properties memperkaku the land where the greater the angle of the slope then the more rigid.